Application of the O-Chat Bot Program to Provide Learning Motivation to National University Students Using AIML: Application of the O-Chat Bot Program to Provide Learning Motivation to National University Students Using AIML - Muhammad Fikri Haikal Husein; Ucuk Darusalam; Andri Aningsih (Institute of Computer Science (IOCS), 2020)
Teaching and learning process raises new problems, some students feel the turmoil in understanding the online-based learning process and the lack of motivation to do the work. With the Chatbot-O Program, students will find it helpful to better understand the online learning process but have not been fully able to build student learning motivation. This study aims to develop to a further stage regarding the Chatbot application to provide motivation to learn at national university students by displaying answer messages based on the questions given. This research uses AIML which is part of the XML set. And also as a language used in composing chatbot logic to understand the input that has been received